Exploring the role of Islamic Fintech in combating the aftershocks of COVID-19: The open social innovation of the Islamic financial system - Mustafa Raza Rabbani; Abu Bashar; Nishad Nawaz; Sitara Karim; Mahmood Asad Moh'd Ali; Habeed Ur Rahiman; Md. Shabbir Alam (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The purpose of the current study is to investigate the role of the Islamic financial system in recovery post-COVID-19 and the way Fintech can be utilized to combat the economic reverberations created by COVID-19. The global financial crisis of 2008 has established the credentials of the Islamic financial system as a sustainable financial system which can save the long run interests of the average citizens around the world while adding value to the real economy. The basic ethical tenets available in the Islamic financial system make it more suited and readymade to fight the economic aftershocks of a pandemic like COVID-19. The basic principles of ethical Islamic finance have solid connections to financial stability and corporate social responsibility within the wide-reaching business context. With the emergence of Financial technology (Fintech) it has provided a missing impetus to the Islamic financial system to compete on equal ground with its conventional counterpart and prove its mettle. The study uses discourse analysis along with the content analysis to extract content and draw a conclusion. The findings of the study indicate that COVID-19 pandemic has provided the opportunity for the social and open innovation to grow and finance world have turned to open innovation to provide a speedy, timely, reliable, and sustainable solution to the world. The findings of the study provide significant implications for governments and policy makers in efficient application of Fintech and innovative Islamic financial services to fight the economic consequences of the COVID-19 pandemic.
Keywords: 650; COVID-19; Islamic banking; Islamic economics; open innovation; social finance; postCOVID-19